Recommendations for Improving Methods and Models for Aquatic Hazard Assessment of Ionizable Organic Chemicals. (24th January 2020) - Escher, Beate I.; Abagyan, Ruben; Embry, Michelle; Klüver, Nils; Redman, Aaron D.; Zarfl, Christiane; Parkerton, Thomas F.
Abstract : pH‐dependence of the toxicity of ionizable organic chemicals (IOCs) is caused by the pH‐dependence of the uptake with constant internal effect concentrations that depend on the mode of action of the IOC, for example, baseline toxicity, uncoupling, or receptor activation. Abstract: Ionizable organic chemicals (IOCs) such as organic acids and bases are an important substance class requiring aquatic hazard evaluation. Although the aquatic toxicity of IOCs is highly dependent on the water pH, many toxicity studies in the literature cannot be interpreted because pH was not reported or not kept constant during the experiment, calling for an adaptation and improvement of testing guidelines. The modulating influence of pH on toxicity is mainly caused by pH‐dependent uptake and bioaccumulation of IOCs, which can be described by ion‐trapping and toxicokinetic models. The internal effect concentrations of IOCs were found to be independent of the external pH because of organisms' and cells' ability to maintain a stable internal pH milieu. If the external pH is close to the internal pH, existing quantitative structure–activity relationships (QSARs) for neutral organics can be adapted by substituting the octanol–water partition coefficient by the ionization‐corrected liposome–water distribution ratio as the hydrophobicity descriptor, demonstrated by modification of the target lipid model. Charged, zwitterionic and neutral species of an IOC can all contribute to observed toxicity, either through concentration‐additive mixture effects or by interaction of different species, as is the case for uncoupling of mitochondrial respiration. For specifically acting IOCs, we recommend a 2‐step screening procedure with ion‐trapping/QSAR models used to predict the baseline toxicity, followed by adjustment using the toxic ratio derived from in vitro systems. Receptor‐ or plasma‐binding models also show promise for elucidating IOC toxicity. The present review is intended to help demystify the ecotoxicity of IOCs and provide recommendations for their hazard and risk assessment. Environ Toxicol Chem 2020;39:269–286. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.